2020
DOI: 10.4236/ce.2020.1110154
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of the COVID-19 Pandemic on the Use of Digital Technologies in Ensuring the Efficient e-Learning Process at the Technical University of Moldova

Abstract: The Technical University of Moldova (TUM) is the only state-accredited technical higher education institution in the Republic of Moldova. In the face of the magnitude of the health crisis, TUM had to quickly adapt its mode of operation to ensure the continuity of its activities and to accompany its students in the study process in an efficient way. In this paper, we analyzed the impact of the COVID-19 pandemic on eLearning and on the use of Moodle and Microsoft 365 educational platforms, implemented at the Tec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 0 publications
1
3
0
Order By: Relevance
“…Most of them (n = 70; 80%) were at least moderately satisfied with their own performance and intend to use online resources after pandemic (n = 79; 90%). This perception is aligned to the current literature that discussed that on-line tools came to stay in the education of future generations pointing to the pandemic as a turning point situation with huge investments of big corporations (Grossi et al, 2021;Wayne et al, 2020, Țurcanu et al, 2020, Mola, 2020.…”
Section: Resultssupporting
confidence: 72%
“…Most of them (n = 70; 80%) were at least moderately satisfied with their own performance and intend to use online resources after pandemic (n = 79; 90%). This perception is aligned to the current literature that discussed that on-line tools came to stay in the education of future generations pointing to the pandemic as a turning point situation with huge investments of big corporations (Grossi et al, 2021;Wayne et al, 2020, Țurcanu et al, 2020, Mola, 2020.…”
Section: Resultssupporting
confidence: 72%
“…The COVID-19 pandemic caused countless setbacks around the world, with significant social and financial effects. UNESCO reported that around one billion students had been compelled to remain at home because of the crisis, and the scale and speed with which schools and colleges had been shut was overwhelming (Giancola and Piromalli, 2020). To face this crisis, even schools and colleges could not stop from transferring their activities to digital platforms (Turcanu et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Rezultatele menționate mai sus arată că pentru ca e-Educația contemporană să fie foarte apreciată trebuie să existe o implicare mai mare a instrumentelor care să permită o gamă largă de interacțiuni între profesori și studenți, precum și dintre studenți [20,21]. Sursa: creat de autor.…”
Section: Sursa: Creat De Autorunclassified